#### Answer

$6$

#### Work Step by Step

RECALL:
$\sqrt[3]{a} \cdot \sqrt[3]{b} = \sqrt[3]{a\cdot b}.$
Use the rule above to have
$\sqrt[3]{-12(-18)}
\\=\sqrt[3]{216}
\\=\sqrt[3]{6^3}
\\=6.$

Published by
Prentice Hall

ISBN 10:
0133186024

ISBN 13:
978-0-13318-602-4

$6$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.